1999
DOI: 10.1093/humrep/14.8.1998
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the male reproductive tract on the reproductive potential of round spermatids abnormally released from the seminiferous epithelium*

Abstract: Round spermatids can be collected from testicular biopsy material or occasionally from semen samples. We evaluated the influence of the passage of round spermatids through the male reproductive tract on their reproductive potential. A model of abnormal release of round spermatids from the seminiferous epithelium was created in mature male rats (group A). Additional sham-treated rats of the same age served as a control group (group B). Round spermatids were collected from the testicles of rats of both groups, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 45 publications
3
31
0
1
Order By: Relevance
“…Androgen deprivation causes loss of sperm motility, fertilization ability, and eventually leads to cell death [Robaire et al 2006]. A decrease in the level of testosterone affects conversion of round spermatids during spermiogenesis at stages 7 to 8 causing premature detachment that prevents elongation [O'Donnell et al 1996;Sofikitis et al 1999], thereby decreasing daily sperm production which may reflect our previous observation of decreased testosterone. Conversely, stress-induced corticosterone release might affect the epididymal microenvironment through the epithelial cytoplasmic and nuclear glucocorticoid receptor [Schultz et al 1993;Silva et al 2010].…”
Section: Figure 8 Sperm Viability (A) Concentration (B) Total Spermentioning
confidence: 61%
“…Androgen deprivation causes loss of sperm motility, fertilization ability, and eventually leads to cell death [Robaire et al 2006]. A decrease in the level of testosterone affects conversion of round spermatids during spermiogenesis at stages 7 to 8 causing premature detachment that prevents elongation [O'Donnell et al 1996;Sofikitis et al 1999], thereby decreasing daily sperm production which may reflect our previous observation of decreased testosterone. Conversely, stress-induced corticosterone release might affect the epididymal microenvironment through the epithelial cytoplasmic and nuclear glucocorticoid receptor [Schultz et al 1993;Silva et al 2010].…”
Section: Figure 8 Sperm Viability (A) Concentration (B) Total Spermentioning
confidence: 61%
“…This effect may be mediated by the loss of the adhesions of the spermatids with the sustentacular Sertoli cells [84]. Studies in our laboratory have demonstrated released step 8 round spermatids within the epididymal lumen of rats with low intratesticular testosterone profiles [83]. It has been proven that lowering of intratesticular testosterone concentration results in the apoptotic death of germ cells [85].…”
Section: Hormonal Mechanisms Regulating Spermiogenesismentioning
confidence: 94%
“…O'Donnell et al [82] and Sofikitis et al [83] have suggested that following withdrawal of intratesticular testosterone in a rat animal model, round spermatids are unable to proceed through the transition between steps 7 and 8 of spermiogenesis and therefore cannot complete the elongation process. This effect may be mediated by the loss of the adhesions of the spermatids with the sustentacular Sertoli cells [84].…”
Section: Hormonal Mechanisms Regulating Spermiogenesismentioning
confidence: 99%
“…Sertoli cells play an essential role in germ cell development in vivo and in vitro, forming niches for germ cells which allow a certain number of germ cells to reside or repopulate the seminiferous tubules, limiting the expansion of spermatogonial population, with each Sertoli cell supporting a defined number of germ cells, and providing essential factors for growth/proliferation and differentiation of germ cells into spermatozoa (Sofikitis et al 1999;Huleihel and Lunenfeld 2004). A relatively constant ratio between Sertoli cells and developed germ cells (premeiotic into spermatids) before and after manipulation (by changing the number of Sertoli cells) has been demonstrated (Simorangkir et al 1995;Orth et al 1998).…”
Section: Sertoli Cell-germ Cell Interactionsmentioning
confidence: 99%
“…In human, FSH induces meiosis entry of spermatogonia and spermiogenesis in co-culture of germ cells-Sertoli cells; this effect was increased by testosterone (Sousa et al 2002). Testosterone was also suggested as a key factor in the regulation of Sertoli cells and spermatids interactions and thus, affect spermiogenesis (O' Donnell et al 1996;Sofikitis et al 1999;Sousa et al 2002).…”
Section: Endocrine Regulationmentioning
confidence: 99%